THE CLINICAL SIGNIFICANCE OF PROCALCITONIN AS A BIOMARKER FOR SEPSIS IN PAEDIATRIC PATIENTS- A PROSPECTIVE OBSERVATIONAL STUDY. - Prasad, Priyanka; Kumar, Anil; Rajiv Ranjan Sinha; Kumar, Rakesh (Student’s Journal of Health Research Africa, 2023)
Introduction: The complicated condition known as sepsis is characterized by life-threatening organ failure brought on by an unbalanced host response to infection. It has received attention for its early detection and rapid supply of antimicrobials because it is linked to considerable morbidity and mortality rates in both adults and children. With higher diagnostic and prognostic utility for bacterial infections, procalcitonin is a recognized biomarker for bacterial sepsis in the non-pregnant population. Method: Children who were admitted between January 2022 and December 2022 to the paediatric intensive care unit at Nalanda Medical College and Hospital with sepsis or septic shock ranged in age from 28 days to 14 years. The children were divided into two groups: the septic shock group (SSG; n = 43) and the sepsis group (SG; n = 47). Procalcitonin levels were assessed at admission (T0) and again 12 hours later (T12h), with the following classifications based on the results: 0.5 ng/mL = sepsis improbable; 0.5 to 2 = sepsis possible; 2 to 10 = systemic inflammation; and 10 = septic shock. Result: At T0, there were more SSG patients in the highest PCT class than SG patients [SSG: 30 (38.9%) > SG: 29 (36.2%); p<0.02]. In comparison to the other classes, the proportion of SSG patients in this highest PCT class was higher (p<0.02; 10 = 38.9%; 2 to 10 = 28.5%; 0.5 to 2 = 28.5%). Procalcitonin behaved similarly at T0 and T12 hours. Conclusion: Sepsis can be distinguished from septic shock by procalcitonin, which can also help with pediatric septic disease diagnosis and may be associated with severity. Recommendation: Along with procalcitonin, other definitive tests must also be conducted in context with information from clinical data for sepsis diagnosis.